2014
DOI: 10.1093/mnras/stu1741
|View full text |Cite
|
Sign up to set email alerts
|

Post-merger evolution of carbon–oxygen + helium white dwarf binaries and the origin of R Coronae Borealis and extreme helium stars

Abstract: Orbital decay by gravitational-wave radiation will cause some close-binary white dwarfs (WDs) to merge within a Hubble time. The results from previous hydrodynamical WD-merger simulations have been used to guide calculations of the post-merger evolution of carbon-oxygen + helium (CO+He) WD binaries. Our models include the formation of a hot corona in addition to a Keplerian disk. We introduce a "destroyeddisk" model to simulate the effect of direct disk ingestion into the expanding envelope. These calculations… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
95
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 70 publications
(102 citation statements)
references
References 65 publications
(104 reference statements)
7
95
0
Order By: Relevance
“…A comparison of the results for KPD 0005+5106 confirms earlier suggestions Wassermann et al 2010) that KPD 0005+5106 is indeed an evolved RCB star. The calculations of Zhang et al (2014) show that the observed C abundance in RCB stars can only be produced by CO WDs in a very narrow mass range (0.55 ± 0.02 M ) merging with a He-WD with a mass in the range 0.3−0.45 M . The total mass should therefore be in the range 0.85−1.1 M , which is similar to observed masses of RCB stars, deduced from the luminosity and evolution calculations (0.8−1.0 M ).…”
Section: Summary and Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…A comparison of the results for KPD 0005+5106 confirms earlier suggestions Wassermann et al 2010) that KPD 0005+5106 is indeed an evolved RCB star. The calculations of Zhang et al (2014) show that the observed C abundance in RCB stars can only be produced by CO WDs in a very narrow mass range (0.55 ± 0.02 M ) merging with a He-WD with a mass in the range 0.3−0.45 M . The total mass should therefore be in the range 0.85−1.1 M , which is similar to observed masses of RCB stars, deduced from the luminosity and evolution calculations (0.8−1.0 M ).…”
Section: Summary and Discussionmentioning
confidence: 98%
“…However, based on arguments from binary population synthesis, only 1% of the RCB stars may form from double He-WDs, and the majority forms from a He-WD + CO-WD merger (see Zhang et al 2014, and references therein). In the cited work, it is demonstrated that post-merger evolution calculations predict surface abundances that can partially explain the observations in RCB stars, in particular for the elements studied in KPD 0005+5106 in the present paper.…”
Section: Summary and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We use a rapid binary evolution code (BSE, Hurley et al 2000Hurley et al , 2002 to evolve these binary systems for 13 Gyr and record the properties of HeWD+MS and HeWD+HeWD mergers. The parameters in the rapid evolution code in this work are chosen to be the same as those previously used to model the rate of double WD mergers in the Galaxy (Han 1998;Zhang et al 2014). Our results are processed to find the properties of a model population with an age of 13 Gyr and a constant star formation rate history of 5 M ⊙ yr −1 , intended to represent the Galaxy (Yungelson & Livio 1998).…”
Section: Population Synthesismentioning
confidence: 99%
“…If the system contains two sufficiently massive white dwarfs or a subdwarf star and a sufficiently massive white dwarf, this evolutionary path can lead to a type Ia supernova (Webbink 1984), the so-called double degenerate scenario. If the total mass of the two merging stars does not exceed the Chandrasekhar limit, He-dominated stars, i.e., R Coronae Borealis stars (RCB), extreme helium (EHe) stars, He-rich subdwarf O (He-sdO) stars or O(He) stars may be produced (Webbink 1984;Iben & Tutukov 1984;Justham et al 2011;Zhang & Jeffery 2012b,a;Zhang et al 2014;Reindl et al 2014b). The existence of planetary nebulae (PNe) around every other O(He) star and the [WN] type central stars, however, put in question the possibility that all He-dominated stars have a merger origin.…”
Section: Introductionmentioning
confidence: 99%